2015
DOI: 10.1002/mrm.25589
|View full text |Cite
|
Sign up to set email alerts
|

MRICEST at 1T with large µeffLn3+ complexes T m3+HPDO3A: An efficient MRI pH reporter

Abstract: In vitro experiments demonstrated the feasibility of the CEST methodology at 1T for nearly every paraCEST candidate under investigation, except for Eu-HPDO3A. Among the studied compounds, Tm-HPDO3A proved suitable for the application of a ratiometric method for assessing pH both in vitro and in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Complexes of L1 and L2 were prepared by following previously described procedures. [ 26,24,20,14,7, À2, À15, À19, À20, À34, À37 ppm;E SI-MS: m/z (%): 242.2 (100) [M/2] 2 + .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Complexes of L1 and L2 were prepared by following previously described procedures. [ 26,24,20,14,7, À2, À15, À19, À20, À34, À37 ppm;E SI-MS: m/z (%): 242.2 (100) [M/2] 2 + .…”
Section: Methodsmentioning
confidence: 99%
“…[27] Using paraSHIFTagents requires the acquisition of af ull spectrum on the MRI scanner and needs somewhat higher concentrationsf or in vivo studies in comparison to paraCEST agents. [26,27] The amide appended-complexess tudied here however, with the exceptiono f[ Co(L1)] 2 + ,a re not suitable as paraSHIFT agents because their non-exchangeable macrocyclic protonsa re broadened due to dynamic processes. Studies of Co II and Fe II complexes containing rigid aromatic pendent groups [2c,d, 8] that produce suitable NMR spectra for paraSHIFT applicationsare underway.…”
Section: Thermometrymentioning
confidence: 98%
“…In a recent study using Yb 3+ -HPDO3A, it was shown that tumor pHe mapping can also provide information about tumor aggressiveness in a rat glioma model [97]. The advantage of PARACEST agents endowed with highly shifted resonances is further witnessed in the case of Tm 3+ -HPDO3A pH-sensitive agent, which allows in vivo tumor pH mapping at lower magnetic fields (1 T), due to the far-shifted hydroxyl resonances of the two diastereoisomers (71 and 185 ppm, respectively) [98]. PARACEST agents possessing two sets of exchangeable protons in the same structure were also investigated by Pagel's group who reported that, in Yb 3+ DO3A-oAA, a complex containing both amide and aryl amine protons, the formation of intramolecular hydrogen bond with a proximal carboxylate ligand resulted in a reduction of the amine exchange rate, thus generating a second CEST effect [99].…”
Section: Paramagnetic Ph-responsive Probes (Paracest)mentioning
confidence: 99%
“…As was shown in the kidney imaging studies, paraCEST agents such as Yb‐HPDO3A (Figure (d)) and Yb‐DO3A‐OAA, Tm‐DOTAM‐Gly‐Lys can be used to produce high resolution pH maps which should be of interest for monitoring tumors . Silvio Aime and colleagues have extended their agent studies into tumor pH mapping .…”
Section: Cest Mri Ph Imaging Applicationsmentioning
confidence: 99%